Post‑caesarean vesicouterine fistula: Youssef’s syndrome a case report - Roy, Tuhin S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Vesicouterine fistula is an uncommon urogynecological fistula, typically induced following lower uterine segment cesarean section, especially an emergency one. The classical clinical features of Youssef’s syndrome are cyclical hematuria, amenorrhea, and urinary continence. The index case reported was a 30 year‐old multipara who had two previous lower segment cesarean sections, underwent a third-time cesarean section and developed urinary incontinence and hematuria on the second week of the post-operative period. CECT urography confirmed vesicouterine fistula. The fistula was managed conservatively.